Kualitas Isi dan Kalimat Efektif pada Buku Antologi Cerpen Berjudul Dibalik Jendela Kamar Ibnu Abbas Terbitan Jejak Publisher sebagai Sumber Bacaan Siswa Kelas 8 SMP - Indah Zahri Rahmawati; Farizka Aziza Ramadhani; Muhammad Fahda Mahasin; Hanifah Ainurohmah; Widi Rahayu; Asep Purwo Yudi Utomo; Mochammad Usman Wafa (Pusat Riset dan Inovasi Nasional, 2024)
The use of effective sentences has a strong influence on the quality of the content of a work. In cerpen writing, it is necessary to use effective language so that both the written and the implied meanings of cerpen can be well conveyed. The study aims to describe the forms of error in the use of sentences effectively in the formation of content quality on cerpen, as well as to present a comprehensive analysis of the linguistic aspects in the cerpen anthology